Range size and seasonal movement for female woodland caribou in the boreal forest of northeastern Ontario - Brown, Glen S.; Mallory, Frank F.; Rettie, James (Rangifer, 2003)
A preliminary examination was conducted of range size and distribution of female woodland caribou (Rangifer tarandus caribou) in northeastern Ontario. Annual and seasonal ranges were calculated using satellite telemetry data collected for 30 female caribou between 1998 and 2001. The mean annual home range size of collared females was 4026 km2. Seasonal ranges varied in size depending on time of year (P<0.05). Calving and summer ranges were significantly smaller than autumn and late winter ranges. Early winter ranges were significantly larger than calving ranges and smaller than late winter ranges. Overall, range sizes of female woodland caribou in northeastern Ontario were larger than those reported for caribou in other Boreal Forest regions across Canada.